WAYS OF INFLUENCING IN HEADLINES: A COMPARATIVE ANALYSIS OF ONLINE MEDIA IN UZBEKISTAN AND KAZAKHSTAN - Tadjibayeva, Dilnoza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The article analyzes the methods of influence used in the headlines of online media outlets in Uzbekistan and Kazakhstan. The research material consists of a corpus of 80 headlines from online publications in Uzbekistan (Gazeta.uz, Podrobno.uz) and Kazakhstan (Nur.kz, Tengrinews.kz). The headlines were selected based on thematic relevance, with 40 from each country. A comparative analysis reveals the most frequently used methods of influence in the headlines of the two media spaces: expressive and evaluative vocabulary, references to personalities and brands, quotations, modal constructions, and compositional divisions of the headline. The results of the study demonstrate that, despite the common set of strategies, the pragmatic implementation of these methods and their frequency of use differ systematically between the two national media spaces. Kazakhstani publications often resort to personalization (mentioning specific names), direct emotional quotations, and the use of colons in segmented headlines to engage readers with the material. Uzbek media tend to be more factual and use generalized subjects and segment headlines with periods to separate opinion from fact. The findings suggest that Uzbek and Kazakh media use similar strategies to influence readers but implement them differently.
Keywords: news headline; headline pragmatics; methods of influence in headlines; Uzbek media; Kazakh media; speech influence; headline structure